Success the psychology of achievement - Olson, Deborah A. PhD (London, UK Dorling Kindersley Limited, 2017)
This expert guide, grounded in psychological research, is for everyone who wants to achieve success on their own terms. Whether you're seeking success in your career, relationships, or everyday life, this unique and inspirational book gives you the tools you need to attain your goals. Full of dynamic infographics and proven psychological strategies, it shows you how to reframe your thinking, capitalize on your resource, and reach your full potential
Chapter 1 A life in progress: the meanings of success and fulfilment -- Chapter 2 Starting with you: positive psychology and the power of beliefs -- Chapter 3 Hone your attitude: exercise your thinking and harness your skills -- Chapter 4 Basic skills for success: an everyday guide to effectiveness -- Chapter 5 In your sights: goal setting and goal getting -- Chapter 6 Success: a whole-life process
Keywords: Success -- Psychological aspects; Self-actualization (Psychology); Self-realization.